Dual localization of Mdj1 in pathogenic fungi varies with growth temperature. (19th February 2014) - Dourado, Ítala Bruna Z.; Batista, Wagner L.; Longo, Larissa V. G.; Mortara, Renato A.; Puccia, Rosana
Abstract: Paracoccidioides brasiliensis and P. lutzii are temperature-dependent dimorphic fungi that cause paracoccidioidomycosis (PCM). Previously, we characterized the Pb MDJ1 gene. This gene encodes P. brasiliensis chaperone Mdj1, which in yeast is a mitochondrial member of the J-domain family, whose main function is to regulate cognate Hsp70 activities. We produced rabbit polyclonal antibody antirecombinant PbMdj1 (rPbMdj1), which labeled the protein not only in mitochondria but also at the cell wall of P. brasiliensis yeasts of isolate Pb18. Here we used anti-rPbMdj1 in confocal microscopy to localize Mdj1 in Pb18 and other fungal isolates grown at different temperatures. Dual intracellular and cell surface pattern were initially seen in yeast-phase P. brasiliensis Pb3, Pb18 (control), P . lutzii Pb01, and Histoplasma capsulatum . Pb18 and Aspergillus fumigatus hyphae as well as Pb3 pseudo hyphae formed at 36°C were labeled predominantly along the cell surface. Preferential surface localization was observed by 72 h of yeast-mycelium thermotransition. It was interesting to observe that anti-rPbMdj1 concentrated at the surface tip and branching points of A. fumigatus hyphae grown at 36°C, suggesting a role in growth, whereas at 23°C, anti-rPbMdj1 was distributed along the hyphal surface. In Pb3, Pb18, and Pb01 mitochondrial extracts, the antibodies revealed a specific 55-kDa band, which corresponds to the processed Mdj1 size. The presence of Mdj1 on the fungal cell wall suggests that this protein could also play a role in the interaction with the host.